Probing the isospin mixing in the 72Kr compound nucleus via GDR γ decay - Agnese Giaz; Oliver Wieland; Angela Bracco; Franco Camera; Soichiro Aogaki; Dimiter L. Balabanski; Maria Brezeanu; Ruxandra Borcea; Marian Boromiza; Ion Burducea; Stefana Calinescu; Adina Coman; et al. (Physics Letters B, 2025)
The isospin mixing was deduced in the compound nucleus 72Kr at a low nuclear temperature around 1.3 MeV, from the γ decay of the giant dipole resonance. The γ rays from two compound-nucleus reactions were measured: from the 32 S + 40Ca at bombarding energy of 90 MeV characterized by isospin I = 0, and from the 31 P + 40Ca at 82 MeV used as a reference. The ELIFANT array was employed at the Bucharest Tandem Laboratory, consisting of Compton-suppressed scintillator detectors. The statistical-model analysis of the measured spectra provided a mixing parameter of (3.5±0.8)%. This new point, being at the lowest temperature compared with the few other existing ones, can validate the predictions of the temperature dependence of the isospin mixing. The isospin-symmetry-breaking correction, δc, used for the Fermi super-allowed transitions was extracted from the present result of the isospin mixing and found to be consistent with β decay data, theoretical predictions, and previous experimental results.